<p>This question is extremely easy. </p>

<p>Q#4 from 2010 PSAT/NMSQT practice test math section 2</p>

<p>Q. If (x-3)(x+3)=a, then (2x-6)(x+3) =</p>

<p>A) 2a

B) 3a

C) 4a

D) 6a

E) 9a</p>

<p>The answer is A. It is easy. However, it took me 45 seconds to do it. By this method:</p>

<p>(x-3)(x+3) = x^2+3x-3x-9 = x^2-9

(2x-6)(x+3) = 2x^2+6x-6x-18 = 2x^2-18</p>

<p>Which is 2a. </p>

<p>But what is the FASTEST method? Is their logic to be imposed in this question to make it answered in less then 30 seconds? What is it?</p>